Национальные обзоры жилищного хозяйства и землепользования - United Nations Economic Commission for Europe (United Nations, 2020)
The Country Profile programme continues to focus on specific challenges or achievements in the housing and land management sectors that are particularly relevant to the country under review. The Country Profile of Belarus focuses on the nation’s housing sector, specifically on issues of housing provision and affordability, management and maintenance of the housing stock, energy efficiency in housing, housing finance, smart sustainable cities, and the legal and institutional framework. The Country Profiles on Housing and Land Management are intended to assist governments to improve the performance of their housing, urban development and land management sectors and, at the same time, to promote sustainable development.